Comparison of surgical trauma between three endoscopic thyroidectomy approaches and open surgery - Qin, Jiali; Ren, Han; Li, Leilei; Wu, YaLei; Xia, TianMing; Wang, Xudong; He, Liang (Frontiers in Oncology, 2025)
ObjectiveThis study aims to conduct a comparative analysis of surgical trauma between three endoscopic thyroidectomy approaches (anterior chest, transoral, and unilateral axillary) and conventional open thyroidectomy (COT) in treating unilateral thyroid carcinoma.MethodsA retrospective analysis was conducted on 200 patients with unilateral differentiated thyroid carcinoma treated at Luoyang Central Hospital affiliated with Zhengzhou University from January 2022 to December 2024. The cohort included 50 patients each: bilateral areolarapproach endoscopic thyroidectomy (BAET), transoral endoscopic thyroidectomy vestibular approach (TOETVA), axillary approach endoscopic thyroidectomy (AAET), and COT. The patients were divided into three groups based on general conditions such as gender, age, and BMI (BAET vs COT; TOETVA vs COT; AAET vs COT).Parameters compared included flap dissection area, perioperative outcomes, postoperative complications, inflammatory markers, postoperative pain (visual analog scale [VAS] score), and cosmetic satisfaction at 3 months;Patients were categorized into normal (BMI < 24 kg/m2) and overweight (BMI > 24 kg/m2) groups for comparison of flap dissection areas.ResultsThe mean age of patients in the three endoscopic thyroidectomy groups was significantly lower than that in the open group (P < 0.05). Flap dissection area, operative time, and postoperative drainage volume were significantly higher in the endoscopic groups than in the COT group (P < 0.05). No significant differences were observed between the three endoscopic thyroidectomy groups and COT in terms of intraoperative blood loss, days to tube removal, length of hospital stay, number of lymph nodes dissected, incidence of surgical complications, perioperative changes in inflammatory markers (interleukin-6, C-reactive protein, and white blood cells), and pain scores at 1 week postoperatively (P > 0.05). However, the TOETVA group exhibited a significantly longer hospital stay and higher VAS pain scores on postoperative day 1 compared with the COT group. No significant differences in these parameters were observed among BAET, AAET, and COT groups (P > 0.05). Cosmetic satisfaction was highest in the TOETVA group, followed by the AAET, BAET, and COT groups. Across all surgical groups, patients with normal BMI exhibited significantly smaller flap dissection areas than those in the overweight group (P < 0.05).ConclusionIn appropriately selected patients, total endoscopic thyroidectomy does not significantly increase surgical trauma compared with COT. It offers improved cosmetic outcomes, which supports its favorable clinical applicability.